Natural history and surgical treatment of chordoma: a retrospective cohort study - Aguiar Júnior, Samuel; Andrade, Wesley Pereira; Baiocchi, Glauco; Guimarães, Gustavo Cardoso; Cunha, Isabela Werneck; Estrada, Daniel Alvarez; Suzuki, Sergio Hideki; Kowalski, Luiz Paulo; Lopes, Ademar (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Chordoma is a rare tumor with a high risk of locoregional recurrences. The aim of this study was analyze the long-term results from treating this pathological condition. DESIGN AND SETTING: Cohort study in a single hospital in São Paulo, Brazil. METHODS: This was a retrospective cohort study on 42 patients with chordoma who were treated at Hospital A. C. Camargo between 1980 and 2006. The hospital records were reviewed and a descriptive analysis was performed on the clinical-pathological variables. Survival curves were estimated using the Kaplan-Meier method and these were compared using the log-rank test. RESULTS: Nineteen patients were men and 23 were women. Twenty-five tumors (59.5%) were located in the sacrum, eleven (26.2%) in the skull base and six (14.3%) in the mobile spine. Surgery was performed on 28 patients (66.7%). The resection was considered to have negative margins in 14 cases and positive margins in 14 cases. The five-year overall survival (OS) was 45.4%. For surgical patients, the five-year OS was 64.3% (82.2% for negative margins and 51.9% for positive margins). In the inoperable group, OS was 37.7% at 24 months and 0% at five years. CONCLUSION: Complete resection is related to local control and definitively has a positive impact on long-term survival.